2011
DOI: 10.1177/097215091101200210
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Customer Satisfaction between Two Indian Retail Brands

Abstract: The present study is an attempt to measure the customer satisfaction of two competitive Indian retail rands and draw a comparison between the two based on customer service quality and value creation. The comparative analysis is drawn using Multiple Regression Model and before that measurement scale has been defined to measure the regressand and the regressors using primary data. The findings include how and to what extent customer service quality and value creation affect customer satisfaction in case of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In their study, store image was composed by a single dimension made up by items related to service, store atmosphere, loyalty programs and service offered by the supermarket. Roy, Bhattacharya, and Sengupta (2011) showed that store image explained 45 percent of the variability of consumer satisfaction. In their study, image comprised physical structure, service reliability and employees' competence and courtesy.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, store image was composed by a single dimension made up by items related to service, store atmosphere, loyalty programs and service offered by the supermarket. Roy, Bhattacharya, and Sengupta (2011) showed that store image explained 45 percent of the variability of consumer satisfaction. In their study, image comprised physical structure, service reliability and employees' competence and courtesy.…”
Section: Discussionmentioning
confidence: 99%
“…On average, it costs a firm five to six times as much to attract new customers as it does to implement retention strategies to hold the existing ones (Lovelock & Wright, 1999). Satisfaction, customer retention and loyalty ensure not only economic success but also sustainable competitive advantage (Roy, Bhattacharya & Sengupta, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Indian retail market which is estimated to almost double from a US$ 330 billion in 2008 to a US$ 637 billion by 2015 (Tripathi, 2008) is giving strong indication of a retail boom for the country as modern retail formats started gaining marketshare since thethe post liberalization era of the 1990s (Akhtar and Equbal, 2012). The real diffusion of organized 4 retail in India started around January 2006 with the announcement of its progressive relaxation policy of 51 per cent FDI in single brand retail (Roy et al, 2011; Singh and Bose, 2011). In terms of share in organized retail, clothing and footwear constituted the highest 41 per cent amounting to ₹ 251 billion with a 14.3 per cent CAGR during 2004–2007 (Joseph et al, 2008).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The store formats include malls, speciality stores, departmental stores, discount stores or the factory outlets, supermarkets, hypermarkets, convenience stores and the category killers in the form of multi-brand stores (Rahman, 2012; Roy et al, 2011). The most popular format that have been adopted earliest in the Indian markets are the malls in the metro cities that range between 60,000 sq.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation